Бронзовая матрица из византийской крепости в Южной Добрудже - Йотов, В. (Материалы по археологии, истории и этнографии Таврии, 2001)
Более десяти лет назад в Исторический музей в городе Добрич поступила бронзовая литая матрица, случайно найденная в византийской крепости вблизи п.Оногур в Южной Добрудже. Она предназначалась для изготовления Т-образных бляшек. На ее лицевой стороне виден геометрический рисунок (окружности, дуги) в разных сочетаниях. Другая сторона имеет грубую, неоформленную поверхность. По форме и орнаменту она близка немногочисленным известным матрицам-моделям для производства блях. A bronze matrix found by chance in Byzantine fortress near the village of Onogur in South Dobrudge was received by History Museum in the town of Dobrich. It was used for manufacturing belt plates and is dated back to the last decade of the 6th - the first decade of the 7th centuries. The latest coins from the fortress (Emperor Maurice, 582 - 602) are dated by the same period. The fortress itself was abandoned after the defeat of organized defence of the Low Danube border at the very beginning of the 7th century. The published matrix testifies to the fact of the existence of local manufacturing details of belt sets.